The Effect Of Financial Performance And Regional Economic Growth Rates On Social Development Indicators In Indonesia - Nuzullestary, Vitriatie; Sutjipto, Hady; Suhendra, Indra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study investigates the impact of regional financial performance and economic growth on key social development indicators in Indonesia, namely poverty, unemployment, and stunting. Using panel data from 34 provinces for 2016–2023, the analysis employs the System Generalized Method of Moments (GMM) to address endogeneity and dynamic panel bias. The results show that Regional Own Source Revenue effectiveness ratio (ER1) significantly reduces poverty and unemployment, indicating that improved revenue realization enhances the fiscal capacity of local governments to provide essential public services and support employment. The regional independence ratio (IR) has a significant negative effect on stunting, suggesting that stronger fiscal autonomy enables better funding for maternal and child health interventions. Economic growth significantly lowers poverty and unemployment but has no significant effect on stunting. Meanwhile, the Gini Ratio exhibits a strong positive effect on stunting, highlighting income inequality as a major barrier to achieving better child nutrition outcomes.